The transition of eldercare responsibility and traditional filial piety concepts and its urban-rural differences in China: an age-period-cohort analysis from 2006 to 2017 - Xiangxiang Liu; Hong-jie Yu; Min-zhe Zhang; Hong-guang Yang; Rui Chen; Litao Zhao; Qi-qiang He (BMC, 2024)
Abstract Background With rapid urbanization, massive migration, and non-family-based eldercare involvement, Chinese concepts of eldercare responsibility and filial piety are shifting. We performed age-period-cohort (APC) analyses to assess the transition of old-age pension coverage, eldercare responsibility, and filial piety concepts and its urban-rural differences among Chinese adults using data from the China General Social Survey (2006-2017). Methods Old-age pension coverage (yes/no) and primary eldercare responsibility (government/offspring/self/sharing) were investigated in 2010, 2012, 2013, 2015, and 2017. Filial piety was evaluated using customized questionnaires in 2006 and 2017. The APC effects were estimated using mixed effects and generalized additive models. Results Among 66,182 eligible participants (mean age: 48.8 years, females: 51.7%) in the six waves, APC analyses indicated that old-age pension coverage increased with aging and over time. Across cohort groups, it grew as the cohort was younger in urban residents but decreased in rural residents. The concept of offspring-based (> 50%) and government/self/offspring-shared eldercare (> 30%) predominated. APC analyses revealed that the offspring-based concept declined with aging (OR = 0.81, 95% CI: 0.79-0.84), whereas the government-based (OR = 1.37, 95% CI: 1.33-1.41) and self-based (OR = 1.55, 95% CI: 1.47-1.63) concepts increased with aging. People born around the 1940s have a comparatively higher possibility to perceive that the primary eldercare responsibility should be undertaken by the government and elder parents. In contrast, people born in the younger cohort were more likely to perceive that adult children are responsible for their parents' primary eldercare. Filial piety score slightly increased with aging (β = 0.18, SD: 0.05) but decreased as the birth cohort was younger. In addition, rural participants were more likely to perceive offspring-based eldercare and maintain filial piety, and the related urban-rural difference was intensified by aging. Conclusions The traditional concept that eldercare solely relies on offspring has changed to relying on multiple entities, including the government and self-reliance. Diluted filial piety in people born in the young cohort requires reinforcement. Moreover, future healthy aging policies need to focus more on urban-rural disparities to promote equity in social well-being.